Characteristics of study plans on the development of research in Peruvian Dentistry - Valenzuela-Torres, Olenka (2019)
Objective. To describe the characteristics of study plans of Peruvian Dentistry faculties regarding the implementation of courses related to scientific research. Methods. A descriptive study that gathered the curricula of the 42 dentistry faculties in Peru until 2019. In each study plan, the following data were collected: type of university, number of years of duration of the profession, number of subjects related to research, semester of the beginning of the research courses and number of courses related to the university thesis. Comparisons of averages and standard errors were made according to type of university (state / private). Results. The average of courses related to the research was 4.5 ± 1.7; being the median of 4 with a minimum value of 1 and a maximum value of 9. Public universities presented a greater number of subjects related to research (5.1 ± 0.6) unlike private universities that presented an average of 1.3 ± 0.2. Two private universities presented more courses with term thesis in their study plans. Conclusions. The state universities presented a greater number of subjects related to research. On average, private universities had a greater number of thesis-related courses.